LAND CERTIFICATION REQUIREMENTS FOR WAQF BASED ON LAW NUMBER 41 OF 2004 CONCERNING WAQF - Lubis, Syaddan Dintara (Hukum tata Negara/Siyasah, 2025)
This research focuses on how laws provide legal certainty for donated properties like privately-owned land. It also investigates the certification procedure of waqf land, from the initial waqf pledge deed to the issuance of a waqf ownership certificate, with attention to the responsible certifying authority. Waqf land without certification is prone to future issues due to uncertain legal status. Many waqf properties eventually fall into other hands because of this ambiguity. As a result, waqf land, intended to support communal welfare, cannot fulfill its economic purpose due to the lack of administrators’ understanding of certification. The objectives include analyzing the Indonesian Waqf Board’s role, identifying obstacles to certification, and tracking the increase in certified waqf land. This study is essential because unresolved legal status can trigger conflicts among donors, managers, or heirs.Keywords: Land Waqf Registration, Waqf Pledge Deed Making Official, Indonesian Waqf Board